A Case of Traumatic Brain Injury Presenting with Musical Hallucinations - Kobayashi, Yasutaka (Case Rep Neurol, 2018)
A 67-year-old woman was hospitalized for rehabilitation from the after effects of a traumatic brain injury. In addition to memory impairment, attention disorder, and executive dysfunction, she experienced musical hallucinations. Brain magnetic resonance imaging revealed cerebral contusion in the bilateral temporal lobes and the left frontal lobe. Case reports of musical hallucinations caused by traumatic brain injury are extremely rare.